Determination of Science Teachers' Level of Relationship with School Guidance and Psychological Counseling Service - Konuk, Murat; Kılıç, Mahmut Sami (Bartin Universitesi, 2025)
The purpose of this study is to examine the perceptions of science teachers, who are class guidance teachers, towards the Psychological Counseling and Guidance service and the services provided by this service in schools within the framework of the theory of planned behavior. According to the theory of planned behavior, attitude towards behavior, perceived behavioral control, subjective values and intention are effective in the emergence of a behavior. In this respect, it is suggested that determining teachers' attitudes towards Psychological Counseling and Guidance (PCG) services, perception of behavioral control, subjective values and norms, and working habits consisting of their intentions regarding the services offered in the organizational structure can affect their organizational decisions. In this context, the variables of attitude, subjective norm and perceived behavioral control, which are considered within the scope of the Theory of Planned Behavior (TPB), were qualitatively evaluated. The data to be used in the study were obtained by applying an interview form containing open-ended questions to 15 teachers working in schools. The data obtained were qualitatively evaluated with descriptive statistics method. As a result, it was determined that the majority of the science teachers had a high level of support from the guidance service, especially in helping students through the reports prepared by the guidance service, cooperating with families, getting to know students and contributing to the solution of problems. In addition, it was concluded that teachers coordinate with the school guidance and counseling service and expect to maintain this relationship, and that the guidance service is important in terms of facilitating their work while carrying out activities. However, it was concluded that teachers were reluctant and inadequate in developing themselves in order to be effective in the field of guidance and counseling services and that they did not do the necessary work.
Keywords: Science Education; Fen Bilgisi Eğitimi; School Counseling; Okul Psikolojik Danışmanlığı